Small peptides from non-edible fish waste with antimicrobial activity - Wonganu Benjamaporn; Roytrakul Sittiruk (E3S Web of Conferences)
Intestine and gill have remained as by-products in fish processing. They can be used to produce various value-added products such as bioactive peptides. This research produced low molecular weight antimicrobial peptides from Tuna protein hydrolysates which were hydrolyzed via pepsin. The protein hydrolysate was passed through a 3kDa cut-off column. The fraction containing ≤ 3 kDa peptides from Tuna hydrolysate had the great ability to inhibit the growth rate of Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923 and Salmonella typhimurium ATCC 13311. The results of antimicrobial activity tests showed that low molecular weight peptides from both intestines and gills affect bacterial growth like a result of the ampicillin test. OFFGEL electrophoresis and C18 column were done to purify peptides following hydrophobic/hydrophilic properties and the isoelectric point (pI). The result revealed that 11.15 mg/mL of hydrophobic peptide hydrolysate from intestines in pH during 3-10and 11.94 mg/mL of hydrophobic peptide hydrolysate from gill in pH 8-10 were able to inhibit the bacterial growths. 8 Peptide sequences from LCMS/MS were synthesized [GGLGVGGY; GLSGWAS; GAQEGSY; ALMAISL; LYMGLAVPL; VILLVAPAS; GGQSTDY; AFSGVEA]. The results revealed that synthesized peptides; GGLGVGGY GLSGWAS have a great 50% inhibitory activity against S. typhimurium ATCC 13311